TAKING IRREGULAR DISTRIBUTION OF POLLUTION AND EVAPORATION COEFFICIENT INTO CONSIDERATION IN DETERMINATION OF INSULATOR SURFACE LEAKAGE CURRENTS - Ozturk, Dursun; Cebeci, Mehmet (Ieee, 2015)
Leakage currents flowing on the insulator surface depend on type and amount of the pollution accumulated on the surface. In this study, insulator leakage currents are simulated with the help of Ant Colony Algorithm (KKA). The pollution layer accumulated on the insulator surface is accepted as pheromones substances of the ants. In regard with this approach, the movement of ants, which are determined based on voltage of each point on the insulator surface, depends on amount of pollution and distance between these points. In the ant colony algorithm, pheromone substance is laid down to the trail of ants randomly and the amount of pheromone is constantly updated by multiplying with a coefficient of evaporation in order to take the evaporation into account. Similarly, the pollution layer on the insulator surface is distributed irregularly and evaporation coefficient is used to refer to a reduction in the amount of pollution caused by formation of dried bands. These bands are caused by the effect of heat produced by the flow of leakage current. The surface conductivity is calculated from the value of pheromone and the leakage current is calculated from conductivity and voltage difference between points by employing a computer software developed in accordance with this algorithm.
9th International Conference on Electrical and Electronics Engineering (ELECO) -- NOV 26-28, 2015 -- Bursa, TURKEY
Keywords: High Voltage Insulator; Pollution Flashover; Dynamic Arc Model; Ant Colony Algorithm